(untitled) (SAARC Journal of Agriculture, 2024)
The fall armyworm, Spodoptera frugiperda J.E Smith, is a worldwide invasive pest of maize, but also damages sweet corn, rice, and sorghum. This pest originates from the Americas and spread to Africa, Asia, and Australia, with more than 80 countries. Pesticidal management practices always get a priority for the immediate intervention of this pest. These practices are against the environment, biodiversity, and human health. Hence efforts are interestingly growing to develop agroecological strategies for fall armyworm management. This review is focused on diagnosing the various agroecological practices that apply to the sustainable management of fall armyworms. The most common pest management practices that are popular among smallholder farmers are intercropping, push-pull systems, crop rotations, mulching, cultural practices, use local pesticidal plants, habitat diversification, soil nutrient management, and many more. Intercropping including push-pull farming systems with leguminous crops reduces the number of fall armyworm eggs by increasing the biological control (BC) activities and inhibits the movement of pest larvae. Mulching on the soil ameliorates soil microclimate and improves plant health. Habitat diversification improves the quality of farms and improve BC activities by providing shelter, nectar, alternative food, and pollen to the pest’s natural enemies. Similarly, local pesticide plants could be a sustainable alternative to synthetic pesticides. Hence, agroecological practices for pest management improve a balanced environment, regulate natural pests, reduce inputs, diversify the agroecosystem, improve biologically mediated soil fertility, increase yields, and finally improve ecosystem services. These practices must be promoted to replace agricultural intensification with sustainable intensification in maize fields. SAARC J. Agric., 22(1): 31-43 (2024)